REDESIGN OF GREEN OPEN SPACES IN SPORTS FACILITIES BY UTILIZING TREE CHARATERISTICS TO ACHIEVE THERMAL COMFORT CASE STUDY: SENTRA PEMBINAAN OLAHRAGA TERPADU (SPORT) JABAR ARCAMANIK - Muliati Putri, Kharisma
Sentra Pembinaan Olahraga Terpadu (SPOrT) is one of the public sports facilities and infrastructure with outdoor spaces that are used by the community to carry out various activities such as light sports and gathering by utilizing the circulation path. The area has limited green areas and the use of unregulated vegetation along the main and secondary circulation routes, as well as a lack of adequate outdoor space for gathering and resting. The purpose of the design is to modify the existing green area of the circulation path and design a new green open space that has the potential for outdoor gathering/plaza and a resting spot through the use of trees based on their characteristics in the green area and to determine their effect on the comfort of the outdoor space. Based on the data obtained from the analysis of existing conditions, it is known that the existing vegetation tends to use trees with low heights, that it does not provide shade which can cause unfavorable thermal sensation conditions on the main circulation path having a road width of > 6 meters. The green area on the secondary circulation path with a road width of 3-4 meters is also not well organized and lacks shade. The northern area of the site which is a fairly large open space is known to be a good area to get the morning sun. The use of trees in green areas to improve the quality of thermal comfort is considered as a solution for utilizing limited green areas. Simulation analysis is then carried out with the help of the ENVI-met program before designing to find out how much air temperature and PET index changes occur with the utilization of the green area of the circulation path into a green path by placing trees that have certain characteristics. It is known that trees with a height of 10-15 meters with round and spreading crowns arranged in a row can improve the thermal comfort conditions better than the use of trees with a height of 5 meters with round and spreading crowns on the main circulation path by utilizing green areas as green path for tree planting. In the secondary path, planting trees with an average height of 5 meters arranged in rows with a spacing of 3-4 meters is also able to improve the condition of thermal comfort. The green path design and the design of new green open space functions are carried out in the east, west, and south areas. There are modifications made to the green area in the form of a green path planted with trees with the characteristics of large trees with a height of 10-15 meters in the main circulation area and trees with a height of 5-10 meters with spreading and round crowns for secondary circulation as an effort to improve thermal comfort conditions in circulation path. The results of the green path design in the area were then retested through the ENVI-met simulation and obtained results in the form of a decrease in average air temperature between 0.01?-1? and an average decrease in PET value of 6.44?. Meanwhile, the landscape design of outdoor space is maximized as green open space for educational and sports functions as well as a mosque plaza which has an outdoor communal space and a resting spot that can support visitor activities by utilizing the combination use of trees with a height of 10-15 meters and trees with a height of 5 meters in the design area in order to achieve a good thermal comfort function.